Barriers to and Facilitators of Older Adult's Adherence to Health Recommendations: Towards an Engaging Two-way Health Communication - Gaspar, Rui (2016)
Non-adherence to health recommendations (e.g. medical prescriptions) presents potential costs for healthcare, which could be prevented or mitigated. This is often attributed to a person’s rational choice, to not adhere. However, this may also be determined by individual and contextual factors implied in the recommendations communication process. In accordance, this chapter focuses specifically on barriers to and facilitators of adherence to recommendations and engagement with the healthcare process, particularly concerning the communication between health professionals and patients. For this, the authors present examples of engagement increment through different degrees of participation, from a one-way/directive towards a two-way/engaging communication process. This focuses specifically on a vulnerable population group with increasing healthcare needs: older adults. Future possibilities for two-way engaging communications are discussed, aimed at promoting increased adherence to health recommendations and people’s self-regulation of their own health.